Olympia, Griechenland - Senff, Reinhard (e-Forschungsberichte des DAI, 2023)
The excavations in Olympia currently focus on the area south of the stadium, where traces of temporary use during the athletic games have come to light as well as remains of a potters’ workshop of the Classical Period. A large number of metal finds, especially parts of weapons could be retrieved from refilled temporary wells. Smaller sondages around the stadium helped to solve problems of date and function of other structures. Architectural reconstructions were carried out in the opisthodomus of the temple of Zeus and the northern column of the ‚Ptolemaic Monument‘ in front of the Stoa of Echos.